Penguatan Budaya Keselamatan Berkendara melalui Seminar Safety Riding dan Layanan Servis Kendaraan Gratis di Desa Kaliurip Purworejo - Aci Primartadi; Dwi Jatmoko; Mike Elly Anitasari; Yuli Widiyono; Dimas Nanda Wibowo; Muhammad Arsyady (Harmoni Sosial : Jurnal Pengabdian dan Solidaritas Masyarakat, 2026)
Riding safety is a key issue in efforts to reduce traffic accident rates. This issue is evident among the residents of Kaliurip Village, where the majority rely on motorcycles as their primary mode of transportation. Observations and coordination with the village government revealed that residents still lack sufficient understanding regarding the importance of periodic vehicle inspections, the use of safety gear, and the practice of orderly traffic behavior. Therefore, this Community Service (PkM) initiative aims to enhance residents' knowledge, awareness, and behavior through a "Safety riding" seminar combined with free vehicle servicing, serving as a form of community empowerment rooted in vocational education. The implementation utilized an Active Community Participation (PAM) approach, engaging residents as active partners throughout the process from problem identification, planning, and execution to program evaluation. Activities included field observations, coordination with the village government, focus group discussions, outreach, safety riding seminars, vehicle inspection demonstrations, free vehicle servicing, and monitoring and evaluation. A participatory approach was selected to boost community engagement and ensure the program's sustainability. The results indicate a highly positive response from the community toward the entire program series. The Safety riding seminar improved residents' understanding of the importance of safety gear, traffic regulation compliance, safe riding techniques, and pre-ride vehicle checks. The free vehicle servicing provided direct benefits through vehicle condition assessments and technical consultations on maintenance. The involvement of the village government, community leaders, students, and lecturers demonstrated the formation of a partnership that supports the program's sustainability.